(untitled) - Perman, Roger (Harlow, Essex, 2011)
Prev. ed. entered under author: Perman, Roger, 1949-; Includes bibliographical references and indexes
Keywords: Environmental economics; Natural resources -- Management; Sustainable development; Kinh tế môi trường; Tài nguyên thiên nhiên -- Quản lý; Phát triển bền vững